Legality in the sphere of implementing executive power in the Republic of Kazakhstan - Balabiyev Кайрат; Akhatov Уалихан; Muratkhanova Меруерт (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The paper considers compliance with the principle of legality of the activities of executive authorities, legislative support and the exercise of powers. The nature and content of the activities of the executive bodies of the territorial level, designed to ensure the implementation of the legal provisions defined by national legislation are studied. The activities of executive authorities include law-making activities in the form of adoption of by-laws, as well as organizational activities. This scope of powers determines the relevance of observing the principle of legality in the activities of executive authorities. The principle of legality preserved through the implementation of joint interaction of local governments with other authorities in solving problems. The introduction of digitalization of public authorities, which acts as one of the ways to prevent corruption offenses in executive authorities and comply with the provisions of national legislation, contributes